Survival of HIV-1 in syringes. - Abdala, N; Stephens, P C; Griffith, B P; Heimer, R (Journal of acquired immune deficiency syndromes and human retrovirology : official publication of the International Retrovirology Association, 1999)
We performed a study to determine the duration of survival of HIV-1 in syringes typically used by injectors of illicit drugs (IDUs). We describe the effectiveness of a microculture assay in detecting viable virus in volumes of blood typical of those commonly found inside used syringes. Using this assay and modeling the worse-case situation for syringe sharing, we have recovered viable, proliferating HIV-1 from syringes that have been maintained at room temperature for periods in excess of 4 weeks. The percentage of syringes with viable virus varied with the volume of residual blood and the titer of HIV-1 in the blood. These experiments provide a scientific basis for needle exchange schemes, harm reduction, and other interventions among IDUs that support the nonsharing and removal of used syringes from circulation.
Keywords: Acquired Immunodeficiency Syndrome; HIV-1; Humans; Reproducibility of Results; Sensitivity and Specificity; Substance Abuse, Intravenous; Syringes